2022
DOI: 10.1111/are.15789
|View full text |Cite
|
Sign up to set email alerts
|

Animal and plant proteins as alternative ingredients in diets for sub‐adult olive flounder Paralichthys olivaceus at farm conditions

Abstract: A 20‐week feeding trial was performed to evaluate the optimum level of animal and plant protein sources as substitutes of fishmeal (FM) in the diets of sub‐adult olive flounder (Paralichthys olivaceus) under farmed conditions. Groups of ninety fish averaging 478 ± 4.7 g (mean ± SD) were randomly distributed into four treatments in triplicates. An FM‐based diet was used as control (CON) and three other diets replaced 20% (APP20), 30% (APP30) and 40% (APP40) of FM with animal (tankage meal and poultry by‐product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…However, neither the SOD nor lysozyme activity of olive flounder was altered by the partial dietary replacement of FM with MM in the current study, demonstrating that the replacement of FM with MM in olive flounder feed had no adverse influence on their innate immune responses. Similarly, the dietary replacement of FM with various animal and plant protein sources did not bring about any adverse impact on the immune responses of olive flounder or red sea bream [9,11,16]. Unlike this study, however, the serum SOD and lysozyme activities of tilapia (Oreochromis niloticus × O. aureus) tended to decrease with increased dietary replacement levels of FM with soybean meal because the immune system of tilapia might be influenced by the certain constituents of soybean meal [47].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…However, neither the SOD nor lysozyme activity of olive flounder was altered by the partial dietary replacement of FM with MM in the current study, demonstrating that the replacement of FM with MM in olive flounder feed had no adverse influence on their innate immune responses. Similarly, the dietary replacement of FM with various animal and plant protein sources did not bring about any adverse impact on the immune responses of olive flounder or red sea bream [9,11,16]. Unlike this study, however, the serum SOD and lysozyme activities of tilapia (Oreochromis niloticus × O. aureus) tended to decrease with increased dietary replacement levels of FM with soybean meal because the immune system of tilapia might be influenced by the certain constituents of soybean meal [47].…”
Section: Discussioncontrasting
confidence: 76%
“…Some studies [5,8] have suggested minimizing the addition of FM to fish feeds based on concerns regarding economic and environmental sustainability. Therefore, it is necessary to identify and look for a replacement that is inexpensive, readily available, and has wellbalanced AA profiles for FM in fish feeds [9,10]. Recently, there has been an increasing number of studies on a novel substitute for FM in fish feeds and research will continue to expand worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method, transportation costs might be avoided, which would lower costs and perhaps promotes both environmental and economic sustainability. To ease the strain from the use of fishmeal, there has been an increase of interest in employing alternative plant sources in fish feed (Choi et al, 2022). Plant-based ingredients are widely utilized in fish diets because they are more readily available and less expensive than fishmeal (Sarfraz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%